Motivational Factors Influencing Telework during the COVID-19 Pandemic - Chittipa Ngamkroeckjoti; Worasak Klongthong; Jakkrit Thavorn (Emerging Science Journal, 2022)
During the COVID-19 pandemic, teleworking has proven to be an effective countermeasure to overcome the spread of this disease while enabling businesses to continue. However, little is known about the extent of their adjustment to daily life routine, interaction among self-control, assignments, family life matters, and coordination with colleagues. This study explores the impact of motivational factors on the performance of teleworkers. An exploratory study was conducted using an in-depth interview with 27 interviewees who work in Thailand and have more than a year of experience switching between being a teleworker and working on-site. The NVivo and SPSS software were performed to reveal deeper data insights and apply non-parametric tests in order to compare findings with various demographic profiles. The findings revealed that environment, time management, and reward are the strongest motivational factors, whereas labour intensity and job security present the weakest relationships with teleworkers’ performance. Numerous implications and strategies to enhance their performance for both organizations and workers are provided. Firms can support a well-prepared environment and manage the flexibility of working time to increase employees’ effectiveness. Moreover, the result-oriented approach can be one of the tools in evaluating their performance rather than attending to their full working time at home. Doi: 10.28991/esj-2022-SPER-016 Full Text: PDF